Fernando González: Walking through his Novel Viaje a pie [Travelling on Foot] - Giraldo Gutiérrez, Francisco Luis; Numpaque Acosta, Andrea María; Londoño Vásquez, David Alberto (Universidad Pedagógica y Tecnológica de Colombia, 2017)
Fernando González is a literary icon of Antioquia, Colombia. His deep and polemic thoughts on the reality of his times are the reason why he is now presented as a highly sensitive writer, regarding social, politic and religious aspects; the latter being the one he complains the most about. Reading his book Viaje a pie [Travelling on foot] feels just like “walking through” the paths he once travelled. This article seeks to comprehend the author’s conception of geography, love and lovelessness, family, politics and religion, in order to characterize him, taking into account the context, events and situations presented in his novel